Cytotoxic potential of waters of the streams Mandacaru, Maringá, Miosótis and Nazareth in the urban area of Maringá, Paraná State, Brazil - doi: 10.4025/actascibiolsci.v34i3.8275 - Elisângela Düsman; Larissa Aparecida Gonçalves; Ana Flávia Reusing; Paula Garcia Martin; Rosinete Gonçalves Mariucci; Veronica Elisa Pimenta Vicentini (Acta Scientiarum. Biological Sciences, 2012)
Streams Mandacaru, Maringá, Miosótis and Nazareth in the urban area of Maringá, Estado do Paraná, Brazil are affected by the local population’s polluting practices. Meristemic cells of Allium cepa L. roots were used as test system to evaluate the cytotoxic effects of the streams’ water. Onion roots were prepared by Feulgen reaction and stained with Schiff's reagent. Statistical analysis of the mitotic index was undertaken with the chi-square test. Results did not show significant cytotoxic effect of water samples. Results may dependent on climate variations, concentration of harmful substances, and on the time and samples sites evaluated. A deeper awareness of the population should be underscored for the proper use, preservation and maintenance of soil and water, with particular emphasis to this region.